1995
DOI: 10.1002/fedr.19951060304
|View full text |Cite
|
Sign up to set email alerts
|

On morphology and taxonomy of the genera Cucumis L. and Melo MILL

Abstract: New evidence, e.g. data from the embryology and flower biology, justify the generic separation of cucumbers and melons into the genera Cucumis and Melo. Species of Melo are phylogenetically more advanced in comparison to taxa of Cucumis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Окремі вегетативно-розмножувані рослини повністю втратили здатність до насінного розмноження. Органи й способи розмноження, а також необхідна термінологія докладно вивчаються у відповідних курсах ботаніки, генетики тощо [9,10].…”
unclassified
See 1 more Smart Citation
“…Окремі вегетативно-розмножувані рослини повністю втратили здатність до насінного розмноження. Органи й способи розмноження, а також необхідна термінологія докладно вивчаються у відповідних курсах ботаніки, генетики тощо [9,10].…”
unclassified
“…Практично усі культивовані рослини, включаючи і P. serrulata, здатні до насіннєвого розмноження, хоча в умовах виробництва деякі з них розмножуються здебільшого вегетативно. Для успішного ведення селекції з тією чи іншою рослиною слід враховувати особливості будови квітки, якість, кількість і способи перенесення пилку та запліднення, ступінь само-і перехресної несумісності, вплив інбридингу, частку перехресного запліднення для самозапильних і частку самозапліднення для перехреснозапильних рослин [9][10][11].…”
unclassified
“…The subgenus melo (30 species, including C. melo), with most of its species in Africa, has a chromosome number n = 12 (Kirkbride, 1993), although there exists several tetraploid and hexaploid forms. Ashurmetov (1995) proposed separating Cucumis into two genera, Cucumis and Melo, but it was not broadly accepted.…”
Section: I21 Genus Cucumismentioning
confidence: 99%
“…Turkey has some unique genotypes, among them can be found several dudaim types or the inodorus kirkagac. Iran also has a wide diversity of the inodorus group that has begun to be analyzed (Kohpayegani, 2004;Kohpayegani and Behbahani, 2008 et al (1986, 1988), Gómez-Guillamón et al (1985, 1995, 1998 and Costa et al (1989). López-Sesé et al (2002, using the RAPD array reported by Staub et al (2000) and SSR loci (Katzir et al, 1996;Danin-Poleg et al, 2001) evaluated a complete set of Spanish accessions.…”
Section: I2113 Molecular Diversity Of Melon Landraces In the Centmentioning
confidence: 99%